2021
DOI: 10.1080/15230430.2020.1859435
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean annual temperatures in 2014–2019 indicate permafrost thaw in Alaskan national parks

Abstract: Rising temperatures in the Arctic can result in thaw of permafrost, with widespread implications for ecosystems and infrastructure. We analyzed mean annual air and ground temperatures in the eight northernmost national parks in Alaska using data from thirty-three National Park Service climate monitoring stations and eight National Weather Service stations. Mean annual air temperatures (MAATs) from 2014 to 2019 increased in a stepwise fashion relative to the preceding thirty-year period by at least 1°C at all l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…FDL are widespread in the valleys in the southern half of Gates of the Arctic National Park, 13,29 within the area where modeling 30 predicts formation of persistent taliks during the current century (shaded gray in Figure 2). As mentioned previously, mean annual ground and air temperatures for the period 2014–2019 were about 2°C above the 30‐year pre‐2014 averages, 31 approximately the predicted amount of change in ground temperatures for the 2050s, based on moderate emission scenarios from a composite of five global climate models 30 . Whether the recent 2°C positive temperature shift will persist in the near future is unknown, but even the warming that has occurred to date may have put other FDL in this region at risk of destabilization like the one shown in Figure 9.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…FDL are widespread in the valleys in the southern half of Gates of the Arctic National Park, 13,29 within the area where modeling 30 predicts formation of persistent taliks during the current century (shaded gray in Figure 2). As mentioned previously, mean annual ground and air temperatures for the period 2014–2019 were about 2°C above the 30‐year pre‐2014 averages, 31 approximately the predicted amount of change in ground temperatures for the 2050s, based on moderate emission scenarios from a composite of five global climate models 30 . Whether the recent 2°C positive temperature shift will persist in the near future is unknown, but even the warming that has occurred to date may have put other FDL in this region at risk of destabilization like the one shown in Figure 9.…”
Section: Discussionsupporting
confidence: 63%
“…The appearance of new RTS is more closely linked to weather 1 and new RTS declined precipitously from episode 2 to 3, as did the area of new ALD, which as discussed above are closely tied to summer weather. The decline in ALD and RTS activity from episodes 2 to 3 occurred in spite of the record high mean annual air temperatures during 2014–2019 31,38 (Figure 3). It is possible that the sites that were most vulnerable to failure did so in the late 2000s (episode 2), and summers were not warm and wet enough to trigger failure at new locations prior to episode 3.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been suggested that colder temperatures in fall may trigger migratory movements [88,89] and, therefore, warmer temperatures associated with climate change might dampen migratory cues for Rangifer in fall. Warmer temperatures are also associated with permafrost degradation [90]. Loss of permafrost can lead to catastrophic lake draining and the development of thermokarst features.…”
Section: Direct Effects Of Changing Temperature and Precipitation Reg...mentioning
confidence: 99%